WAYS TO USE SOLVENTS OBTAINED FROM INDUSTRIAL WASTE (Scientific journal of the Fergana State University, 2026)
This article describes the separation of the gasoline fraction (toluene concentrate) at a temperature of 90-115оС, which includes a solvent obtained by mixing the product of the transesterification of distillery waste (cube residue) with acetic acid in a ratio of 60÷40.